In stone and story: early Christianity in the Roman world - Longenecker, Bruce W. (Baker Academic, 2020)
This beautifully designed, full-color textbook introduces the Greco-Roman background of the New Testament by immersing students in the life and culture of the thriving first-century towns of Pompeii and Herculaneum, which act as showpieces of the world into which the early Christian movement was spreading.